2014
DOI: 10.1016/j.phytochem.2014.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Stable, water extractable isothiocyanates from Moringa oleifera leaves attenuate inflammation in vitro

Abstract: Moringa (Moringa oleifera Lam.) is an edible plant used as food and medicine throughout the tropics. A moringa concentrate (MC) made by extracting fresh leaves with water utilized naturally occurring myrosinase to convert four moringa glucosinolates (1–4) into moringa isothiocyanates (5–8). Optimum conditions maximizing MC yield, compound 5 (4-[(α-L-rhamnosyloxy)benzyl]isothiocyanate), and compound 8 (4-[(4’-O-acetyl-α-L-rhamnosyloxy)benzyl]isothiocyanate) content were established (1:5 fresh leaf weight to wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
150
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 172 publications
(164 citation statements)
references
References 41 publications
(17 reference statements)
9
150
2
3
Order By: Relevance
“…Compounds 1 and 4 were previously purified in our laboratory from a methanolic extract of fresh moringa leaves by HPLC as described by Waterman et al 8 The chemical purity of isolated ITCs was confirmed by LC-MS and 1 H NMR analyses. 8 …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Compounds 1 and 4 were previously purified in our laboratory from a methanolic extract of fresh moringa leaves by HPLC as described by Waterman et al 8 The chemical purity of isolated ITCs was confirmed by LC-MS and 1 H NMR analyses. 8 …”
Section: Methodsmentioning
confidence: 99%
“…The MS data obtained for the ITCs ( 1 – 4 ) gave the expected m / z values and fragment ions that were characteristic for these compounds. 8 In the current study, the quantification of ITCs in the fractions were done by using standard curves generated for pure 1 and 4 , which were purified (>98%) previously as described by Waterman et al 8 Briefly, 1 µL LC-MS injections of compound 1 at 20, 100, and 200 ng/µL generated a standard curve ( y = 123 x − 0.098, R 2 = 1), and injections of compound 4 at 10, 50, and 100 ng/µL generated a standard curve ( y = 104.32 x − 0.098, R 2 > 0.99). The concentrations of compounds 2 and 3 in the fractions and crude extract were estimated by using the standard curve of compound 4 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations